The great Padma : the epic river that made the Bengal Delta - Ashraf, Kazi Khaleed (Bengal Institute for Architecture, Landscapes and Settlements ; ORO Editions, 2023)
"The first comprehensive book on the River Padma, considered the last leg of the Ganges, with a rich collection of new photographs and maps. The Great Padma Book defines the life and history of the Bengal Delta, the largest delta in the world. The book contains original essays by well-known writers, researchers, and academics from diverse fields, including geography, history, literature, architecture, and food history. The preface is written by the renowned author Amitav Ghosh (The Hungry Tide). Besides unpublished photographs documenting the magnificence and diversity of the great river, and wonderful set of maps and diagrams, the book has a rich content in depicting the life and times related to this turbulent river. The wonderful design and layout of the book will make this a collectable item"--Publisher's description.